Perlindungan Hukum Terhadap Anak dari Kejahatan Terorisme di Wilayah Hukum Provinsi Jambi - Ferdricka Nggeboe; Reza Iswanto; Sriayu Indah Puspita (Universitas Batanghari Jambi, 2022)
The crime of terrorism is currently growing, so that the government, law enforcement officers, the community and children need to be vigilant so that they can avoid this terrorism crime. For this reason, this study was conducted to determine the legal protection provided by the Terrorism Prevention Coordination Forum (FKPT) and Jambi Province law enforcement officers. The object of this research is the legal protection of children. The research method used in this study is empirical juridical so that this research is more descriptive, the data sources are field research and literature, the sampling technique is done by purposive sampling, the data collection techniques are observation and interviews and analyzed qualitatively. The results showed that legal protection for children from terrorism crimes in the jurisdiction of Jambi Province, namely the Terrorism Prevention Coordination Forum (FKPT) carried out preventive efforts in the form of socializing children in Jambi Province regarding the dangers of terrorism crimes including their recruitment and providing medical assistance and rehabilitation for crime victims. terrorism and compensation for the families of victims of terrorism crimes, while repressive efforts are in the form of imposing criminal sanctions on perpetrators of terrorism crimes in Jambi Province.